2016
DOI: 10.1159/000443174
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Verbal and Visuospatial Working Memory Performance and Networks

Abstract: Background: Working memory (WM) has been a matter of intensive basic and clinical research for some decades now. The investigation of WM function and dysfunction may facilitate the understanding of both physiological and pathological processes in the human brain. Though WM paradigms are widely used in neuroscientific and psychiatric research, conclusive knowledge about potential moderating variables such as gender is still missing. Methods: We used functional magnetic resonance imaging to investigate the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 61 publications
4
35
1
3
Order By: Relevance
“…A recent fMRI study on Sternberg task obtained different results from ours and reported that women exhibited disadvantages with stronger activation compared to men . The main reason for the disagreement between this study and our study may be that the study restricted men and women using specific strategies refer to their instructions, while our experiment did not impose such restrictions so that participants could use their preferred strategies.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…A recent fMRI study on Sternberg task obtained different results from ours and reported that women exhibited disadvantages with stronger activation compared to men . The main reason for the disagreement between this study and our study may be that the study restricted men and women using specific strategies refer to their instructions, while our experiment did not impose such restrictions so that participants could use their preferred strategies.…”
Section: Discussioncontrasting
confidence: 86%
“…Few researches investigated gender differences in brain functions using Sternberg task . These studies were based on functional magnetic resonance imaging (fMRI) observations of the blood‐oxygen‐level‐dependent signals.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have used fMRI techniques to evaluate sex differences in young healthy subjects while performing verbal and VSWM tasks (Zilles et al, ). Their results showed that females exhibited disadvantages in both working memory domains accompanied by stronger brain activation patterns, which was interpreted as a reflection of a slightly lower working memory capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Gender differences in WM of young healthy subjects have been reported, indicating a male advantage in this memory, with females exhibiting disadvantages with a small effect size in both verbal and visuospatial WM (Zilles et al, 2016). This male advantage could be explained by activating effects of testosterone (Janowsky et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This male advantage could be explained by activating effects of testosterone (Janowsky et al, 2000). Nevertheless, age and specific task modulate the magnitude and direction of the effects (e.g., Zilles et al, 2016; Voyer et al, 2017). This kind of differences is not so clear in IVM.…”
Section: Introductionmentioning
confidence: 99%